Microbiological evaluation of the steam sterilization of assembled laparoscopic instruments - Tamara Carolina de Camargo; Kazuko Uchikawa Graziano; Alda Graciele Claudio dos Santos Almeida; Karina Suzuki; Cely Barreto da Silva; Flávia Morais Gomes Pinto
ABSTRACT Objective: assess the safety of steam sterilization of assembled laparoscopic instruments with challenge contamination. Method: a laboratory experimental study, using as test samples trocars and laparoscopic graspers. Geobacillus stearothermophillus ATCC-7953 was used, with a microbial population of 106UFC/Filter paper substrate, removed from the biological indicator. Three of them were introduced into each instrument at the time of assembly, and sterilized at pressurized saturated steam, 134oC for 5 minutes. After sterilization, the instrument was disassembled and each filter paper substrate was inoculated in soybean casein culture and incubated at 56oC for 21 days. In case of absence of growth, they were subjected to heat shock of 80oC, for 20 minutes and re-incubated for 72 hours. Sample size: 185 graspers and 185 trocars, with 95% power. We paired the experiments with comparative negative control groups (5 graspers and 5 trocars with challenge contamination, sterilized disassembled) and positive control (30 filter paper supports, unsterilized), subject to the same incubation procedures. Results: there was no microbial growth in experimental and negative control. The results of the positive control were satisfactory. Conclusion: this study provided strong scientific evidence to support the safety of steam sterilizing of the assembled laparoscopic instrument.